Cover Image: Volume 2 Issue 2. Issue 2 (3rd April 2023) - Brocks, Oliver; Stasiak, Adam; Biedinger, Jan; Wortmann, Martin; Blachowicz, Tomasz; Kaschuba, Reinhard; Ehrmann, Andrea
Abstract : Electrospun nanofiber mats were coated with a thin magnetic layer, the magnetization in which is shown by fields of small arrows. Measuring this magnetization and its reversal under a varied external magnetic field is performed by a magneto‐optical method, as shown by the impinging and reflected green laser beams. The paper reports for the first time such magneto‐optical measurements on chaotically distributed nanofibers, leading to unusual hysteresis loop shapes. Read the article here (https://onlinelibrary.wiley.com/doi/10.1002/appl.202200113 ).